2021
DOI: 10.1038/s41598-021-85397-x
|View full text |Cite
|
Sign up to set email alerts
|

Controlling metal–insulator transitions in reactively sputtered vanadium sesquioxide thin films through structure and stoichiometry

Abstract: We present a study of $$\hbox {V}_{2}\hbox {O}_{3}$$ V 2 O 3 thin films grown on c-plane $$\hbox {Al}_{2}\hbox {O}_{3}$$ Al 2 O … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 35 publications
4
15
0
Order By: Relevance
“…The coherence length as a function of f R is also presented in figure 2(d). The above analysis of the epitaxial quality of films is in good agreement with the data obtained via reciprocal space mapping and the phi-scan profiles (not shown here) and has already been explored in our earlier work over similar structures [10,30], fabricated via dcMS sputtering.…”
Section: Structural Characterizationsupporting
confidence: 87%
See 3 more Smart Citations
“…The coherence length as a function of f R is also presented in figure 2(d). The above analysis of the epitaxial quality of films is in good agreement with the data obtained via reciprocal space mapping and the phi-scan profiles (not shown here) and has already been explored in our earlier work over similar structures [10,30], fabricated via dcMS sputtering.…”
Section: Structural Characterizationsupporting
confidence: 87%
“…Figure 2(b) shows XRD scans for varying O 2 flow rates for the dcMS deposited films, at constant power of 150 and 200 W. The epitaxial nature obtained by dcMS deposition is found to be strictly dependent on both the power setting and specific O 2 flow rate [10]. That is, films deposited at 200 W with a 1.5 sccm O 2 flow rate showed similar structural quality (epitaxial nature) as that obtained at a lower power and O 2 flow setting of 150 W and 1.0 sccm, respectively.…”
Section: Structural Characterizationmentioning
confidence: 97%
See 2 more Smart Citations
“…Such highly crystalline hybrid heterostructures of this type have not been reported previously in the literature. Previously, we have shown that the epitaxial nature of V 2 O 3 films grown by dc-magnetron sputtering is strongly dependent on the power settings, O 2 flow rate and other deposition parameters [21]. These results reveal the film layering to be extremely well defined with very low roughness.…”
Section: Structural Propertiesmentioning
confidence: 76%